Bench‐scale Analysis of Surrogates for Anaerobic Digestion Processes. (1st May 2016) - Carroll, Zachary S.; Long, Sharon C.
ABSTRACT: : Frequent monitoring of anaerobic digestion processes for pathogen destruction is both cost and time prohibitive. The use of surrogates to supplement regulatory monitoring may be one solution. To evaluate surrogates, a semi‐batch bench‐scale anaerobic digester design was tested. Bench‐scale reactors were operated under mesophilic (36 °C) and thermophilic (53–55 °C) conditions, with a 15 day solids retention time. Biosolids from different facilities and during different seasons were examined. USEPA regulated pathogens and surrogate organisms were enumerated at different times throughout each experiment. The surrogate organisms included fecal coliforms, E. coli, enterococci, male‐specific and somatic coliphages, Clostridium perfringens, and bacterial spores. Male‐specific coliphages tested well as a potential surrogate organism for virus inactivation. None of the tested surrogate organisms correlated well with helminth inactivation under the conditions studied. There were statistically significant differences in the inactivation rates between the facilities in this study, but not between seasons.